Pengaruh Disiplin Kerja Terhadap Kinerja Guru SMA Negeri 3 Kota Bima: The Effect of Work Discipline on The Performance of Teachers at SMAN 3 Kota Bima - Muhsin, Muhsin; Yusuf, Muhammad; Irawan, Ikbal (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to determine the effect of work discipline on teacher performance at SMAN 3 Kota Bima. The research instrument used a Likert-scale questionnaire. The sample in this study was 35 respondents using a purposive sampling technique. Data collection techniques used were observation, questionnaires, and literature review. Analysis used simple linear regression. The results showed that work discipline significantly influenced teacher performance at SMAN 3 Kota Bima.